Estrategias de la Lectoescritura para Fortalecer las Conciencias Lingüísticas en los Niños de Preparatoria. - Amaya Guilcamaigua, Mercy Alexandra (2022)
The work carried out is based on the methodology of literacy for the development of comprehensive reading of high school children. Its general objective is to strengthen the teaching - learning process in high school children, through the application of literacy strategies for the development of methodological or recreational activities, where the beneficiaries will be the children and the teachers, the approach is quantitative that It allowed to observe the behaviors as the effects and causes of the methods, it gave as main results the low performance in each of their activities that they carried out jointly with their teacher, the same one that denoted the interest to participate and to develop their autonomy by themselves. because the activities were theoretical and not practical. Therefore, the proposal of a guide of Playful Literacy Strategies to Strengthen Linguistic Awareness in High School Children was proposed, the same that was applied and excellent results were obtained in all high school children, therefore it is concluded that, the strategies used can be applied through playful activities that will help improve the development of teaching - learning of high school children, changing the monotonous part for games where the interest to participate and learn with these activities will be called, the results obtained, after the proposal they have been very favorable in high school children, therefore, boys and girls improved their comprehensive reading, through the application of didactic or playful activities